Academic Self-problems of Candidate Teachers of Native Language: I am not sure what or how to learn. But I must be sure of what I can teach. - Orhan, Belkis; Demir, Sezgin (Ani Publishing, 2024)
Academic self-concept is an individuals' self -definition using their experiences in the educational process or their views on their own skills and interests. This study aims to determine the academic self -perception of teacher candidates of native language. This study was conducted with qualitative approach in a phenomenological design. The study group consisted of 10 female and 6 male native language teacher candidates at a university located in the eastern part of Turkey. During the data collection process, semi -structured interviews were conducted with open-ended questions, the data collected with a voice recorder was converted into written text. Participant views were subjected to content analysis. The first, last, and focus codings were completed for coder reliability; and an external controller was also used. In this study, the data source was diversified with reminder notes and observation reports for stability and transparency. The findings revealed that most participants had high verbal abilities and interests, and weak numerical abilities and interests. Additionally, the views that they were unable to make the right choices line with their abilities and interests and therefore could not achieve their academic self-concept and goals are remarkable.
Keywords: Academic self-concept; native language education; teacher candidate